Efficacy and acceptability of treatment to eradicate nasal Staphylococcus aureus carriage among haemodialysis patients. Issue 7 (24th April 2019) - Ritchie, Stephen R; Burrett, Emma; Priest, Patricia; Drown, Juliet; Taylor, Susan; Wei, Jason; Collins, John; Thomas, Mark G
ABSTRACT: Aim: For patients requiring haemodialysis, the risk of Staphylococcus aureus disease is higher in those colonized and persists while the person requires haemodialysis, necessitating frequent decolonization. However, the duration of successful decolonization is not known. This study aimed to determine the duration of efficacy of decolonization in intermittent and persistent S. aureus carriers requiring haemodialysis using two decolonization strategies. Methods: We screened 100 outpatients requiring haemodialysis for S. aureus carriage and then decolonized 14 intermittent carriers and 18 persistent carriers. Participants were invited to undertake two decolonization attempts, using systemic or topical antibiotics 12 weeks apart. Nasal swabs were taken weekly to determine the duration of successful decolonization. Results: Decolonization was successful in 24/32 (75%) participants and the median duration of decolonization was 35 days (95% confidence interval (CI) 11–59). The median duration of S. aureus decolonization was significantly shorter for persistent carriers (19 days, 95% CI 13–25 days) in comparison with intermittent carriers (70 days, 95% CI 61–79 days; P  < 0.01). 28/52 (54%) post‐decolonization surveys indicated that they would use the treatment again, 14/52 (27%) surveys indicated that they would not use the treatment again, and 10/52 (19%) were undecided. 16/53 (30%) decolonization attempts resulted in an adverse drug reaction. Conclusion: Staphylococcus aureus decolonization using topical or systemic treatments was successful for many haemodialysis patients, and provided a month free of S. aureus colonization. Although decolonization treatment provided a shorter duration of success for persistent carriers in comparison with intermittent carriers, persistent carriers are likely to gain the most from effective decolonization strategies. Summary at a Glance: Patients on haemodialysis who are colonized with S. aureus have a higher risk of disease caused by the organism. This study reports the efficacy of systemic and topical decolonization strategies.